Bibliometric and scientometric analysis of PSMA-targeted radiotheranostics: knowledge mapping and global standing - Sallam, Mohamed; Mohammadi, Mahan; Sainsbury, Frank; Nguyen, Nam-Trung; Kimizuka, Nobuo; Muyldermans, Serge; Benešová-Schäfer, Martina (Frontiers in Oncology, 2024)
Abstract Purpose Bibliometric and scientometric analyses provide a structured approach to large amounts of data, enabling the prediction of research theme trends over time, the detection of shifts in the boundaries of disciplines, and the identification of the most productive countries, institutions and scholars. In the context of prostate-specific membrane antigen (PSMA)-targeted radiotheranostics, no bibliometric or scientometric analysis has been published thus far. Therefore, this study was conducted to identify key contributors to the literature, assess the global scientific production of related research, and possibly predict future development patterns. Methods Scientometrics and bibliometrics were utilized to analyse the current body of knowledge while tracking its evolution to support scientific decision-making comprehensively and systematically. Science mapping techniques were employed to visualize research activities. Two different tools, Tableau and VOSviewer, were utilized, with VOSviewer being deemed the most suitable for the research objectives. The Web of Science (WoS) was used as the principal database for the searches. Results Through the search process over a period of 30 years (January 1993–January 2023), 694 original studies in the English language were subjected to comprehensive analysis. By employing bibliometric and scientometric methods, multiple networks were created that mapped various concepts, such as publication trends, leading countries, cocitations, coauthorship among researchers and scientists, as well as coauthorship among organizations and funding agencies. This study revealed the evolutionary patterns, trends, outliers, and key players in the PSMA field, which enabled a more nuanced understanding of the research landscape. Conclusion This research contributes to the enrichment of knowledge on PSMA-targeted radiotheranostics through detailed global bibliometric and scientometric analyses. It stresses the necessity for the development of communication platforms, the establishment of supportive infrastructures, and the implementation of proactive solutions to address emerging challenges. This study offers a significant resource for delineating effective strategies and identifying prominent funding bodies essential for continuous advancements in the field of PSMA-based diagnosis and therapy for prostate cancer. It is vital to sustain this momentum to ensure further progress in this pioneering area.